Allergen component analysis as a tool in the diagnosis of occupational allergy. Issue 2 (April 2016) - Raulf, Monika
Abstract : Purpose of review: Rapid developments have been seen in molecular allergy diagnosis, based on the detection and quantification of specific IgE to single allergens. This review summarizes and discusses studies on allergen component analysis as a tool in the diagnosis of occupational allergy. Recent findings: More than 400 agents are identified as sensitizers of occupational asthma, but only very few are characterized on the molecular level and available for routine diagnosis. Baker's asthma is one of the most frequently occurring forms of occupational asthma caused by workplace-related inhalation of cereal flour mainly wheat. Wheat sensitization profiles of bakers show great interindividual variability and no wheat allergen could be classified as the major allergen. Component-resolved diagnosis is a useful tool for diagnosing natural rubber latex (NRL) allergy. In cases with unexpected high-latex IgE but without clinical symptoms application of crossreactive carbohydrate determinants are helpful to clarify the cause of IgE binding. Summary: Latex is an excellent model for component-resolved diagnosis and demonstrates well how to improve the diagnosis by using single allergens. For diagnosis of baker's asthma, a whole wheat extract is still the best option for specific IgE determination, but single wheat allergens might help to discriminate between wheat-induced food allergy, grass-pollen allergy, and baker's asthma. New diagnostic tools and platforms are promising, but further knowledge of molecules relevant for occupational asthma (as in wood dust allergens, enzymes, laboratory animal allergens, etc.) and for occupational hypersensitivity pneumonitis is necessary to improve and standardize the diagnostic tools.